Rencana Pelaksanaan Pembelajaran (RPP) in learning entrepreneurship subjects at SMAN 1 Lembang - Bella Putri Iskandar; Nabil Fatya NH; Naia Dwi Anindita (Universitas Pendidikan Indonesia, 2024)
The lesson plan or Rencana Pelakssanaan Pembelajaran (RPP), serves as a crucial guideline for educators at SMAN 1 Lembang, especially in teaching the subject of entrepreneurship. The continuity of this learning process is essential, considering the rapid dynamics in the business and economic world, requiring students to be skilled in facing future challenges. This research aims to evaluate the school's effectiveness, design, implementation, and evaluation of the Entrepreneurship RPP. The research method uses a qualitative approach with interviews, observation, and documentation studies. Researchers collected data from the internet and sources, namely teachers or teaching staff at SMAN 1 Lembang. The research findings indicate that the effectiveness of learning is closely related to well-planned and implemented RPP, supported by teaching methods suitable for the components of the subject matter. A well-structured RPP serves as a practical guide to achieving learning objectives. Teachers must be selective in choosing teaching methods that align with the needs and content. This research emphasizes the importance of RPP as a supporting tool in directing structured and effective learning at SMAN 1 Lembang, contributing to enhancing educational quality in the school.